Insomnia Symptoms, Daytime Naps And Physical Leisure Activities In The Elderly: FIBRA Study Campinas - Natália Tonon Monteiro; Anita Liberalesso Neri; Maria Filomena Coelim (SciELO, 2014)
The practice of physical activities contributes to reducing the risk of chronic diseases and improves sleep patterns in the elderly. This research aimed to investigate the association between insomnia symptoms and daytime nap and the participation in physical leisure activities in elderly community residents. Data from the Studies Network of the Fragility in Brazilian Elderly (Campinas site), were used. Information from 689 elderly was analyzed, regarding sociodemographic characterization, physical leisure activity, occurrence of daytime napping and its duration, symptoms of insomnia and use of sleep medication. A significant association was found between the practice of walking and the daytime nap of short duration. Studies indicate that a short nap can benefit the quality of sleep and health of the elderly. Therefore, promoting the practice of walking can be a nursing intervention that favors the sleep patterns of the elderly.